Radiological and clinical evaluation of triple combination modulating therapy effectiveness in adult patients with cystic fibrosis - Corrado Tagliati; Stefano Pantano; Giuseppe Lanni; Davide Battista; Federico Cerimele; Francesca Collini; Alberto Rebonato; Roberto Esposito; Matteo Marcucci; Marco Fogante; Giulio Argalia; Cecilia Lanza; et al. (Meta-Radiology)
Objectives: Previous studies showed the clinical effectiveness of elexacaftor-tezacaftor-ivacaftor (ETI) in cystic fibrosis (CF) patients and a recently published study evaluated twelve CF patients that performed chest and sinus computed tomography (CT) examinations and showed that ETI decreased pulmonary and sinus morphological abnormalities after one year of treatment. The aim of the present study was to evaluate the role of CFTR modulator therapy in improving radiological and clinical scores one year after ETI therapy initiation in a wider CF patient population. Materials and methods: Between January 2020 and December 2022, 44 CF adult patients received elexacaftor-tezacaftor-ivacaftor (ETI) therapy for at least one year and underwent a chest CT examination at our hospital before and one year after ETI therapy initiation. Experienced radiologists who were blinded to the treatment assessed the images in consensus. The Brody-II score (BSII), the Lund-Mackay score (LM score) and the Sheikh-Lind CT sinus disease severity scoring system (SL score) were evaluated. Clinical scores such as cystic fibrosis clinical score (CFCS), Cystic Fibrosis Questionnaire-Revised (CFQ-R) score, the 22-item SinoNasal Outcome Test (SNOT-22) questionnaire and the CF-specific 28-modal abdominal symptom score (CFAbd-Score) were evaluated. Forced expiratory volume in 1 ​s (FEV1) and forced vital capacity (FVC) were also assessed. Paired samples t-tests were used to compare differences before and after one year of ETI therapy initiation, and Pearson's correlation coefficient was used to evaluate changes in FEV1 and total BSII and in FVC and total BSII. Results: Total BIIS one year after ETI initiation showed statistically significant lower scores (−6.0 p, p ​< ​0.0001). In particular, mucous plugging (−15.8 p, p ​< ​0.0001), peribronchial thickening (−16.2 p, p ​< ​0.0001) and parenchyma (−0.3 p, p ​= ​0.0397) showed statistically significant lower scores. LM score, SL score, FEV1, FVC, CFCS, CFQ-R, SNOT-22 and CFAbd-Score showed statistically significant lower scores one year after ETI initiation (p ​< ​0.0001). The correlation between ΔFEV1 and Δtotal BSII was statistically significant and moderate (r ​= ​−0.5188, p ​= ​0.0003), and the correlation between ΔFVC and Δtotal BSII was statistically significant and weak (r ​= ​−0.3160, p ​= ​0.0367). Conclusion: Evolution of imaging findings on CT during follow-up closely correlate with improved clinical scores and functional data one year after ETI therapy initiation, indicating that CT may be a useful adjunct during follow-up of CF patients under this treatment as an objective measure of disease improvement.